Direct imidation of lactones via catalytic oxo/imido heterometathesis. Issue 21 (15th February 2021) - Rumyantsev, Andrey V.; Pichugov, Andrey V.; Bushkov, Nikolai S.; Aleshin, Dmitry Yu.; Strelkova, Tatyana V.; Lependina, Olga L.; Zhizhko, Pavel A.; Zarubin, Dmitry N.
Abstract : We report the first examples of catalytic oxo/imido heterometathesis reactions that involve carboxylic acid derivatives (lactones). Abstract : We report the first examples of direct imidation of lactones giving the corresponding cyclic imidates via oxo/imido heterometathesis with N -sulfinylamines catalysed by a well-defined silica-supported Ti imido complex.